2013
DOI: 10.1017/s2078633613000027
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of the Azikheli buffalo in Pakistan

Abstract: This study aims to characterize Azikheli, an undocumented buffalo breed, in its home tract (Khwazakhela, Swat, Pakistan) under traditional farming conditions. For this purpose, 108 buffalo cows and 27 bulls were randomly selected. Mean, standard error, Student's t test and Chi-square test were used for various comparisons. The results show that the majority of animals have a brown coat colour. Cows have significantly higher heart girths, longer horns, longer necks and wider faces at the level of the eyes than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
4
17
2
Order By: Relevance
“…Under farm conditions the body length in swamp buffalo was little higher as reported by Goswami (2009). Khan et al (2013) reported body length to be 140.39+0.94 and 147.89±2.60 cm respectively in Azikheli buffalo cows and bulls of Pakistan, similar findings (147.3±7.2 cm) were reported by in adult Nili-Ravi buffalo cows in commercial farms of Pakistan. Siddique et al (2010) observed the body length of swamp buffalo calves and adult females in Trishal sub district of Bangladesh being 53.11±1.05 cm and 126.22±7.10 cm respectively which is lower than the present findings.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Under farm conditions the body length in swamp buffalo was little higher as reported by Goswami (2009). Khan et al (2013) reported body length to be 140.39+0.94 and 147.89±2.60 cm respectively in Azikheli buffalo cows and bulls of Pakistan, similar findings (147.3±7.2 cm) were reported by in adult Nili-Ravi buffalo cows in commercial farms of Pakistan. Siddique et al (2010) observed the body length of swamp buffalo calves and adult females in Trishal sub district of Bangladesh being 53.11±1.05 cm and 126.22±7.10 cm respectively which is lower than the present findings.…”
Section: Resultssupporting
confidence: 83%
“…The average body height at wither observed in the present study for 2-3 years male and 4 years and above female swamp buffaloes were lower than the findings of Gurkan et al (2011) in Anatolian water buffaloes of Turkey. In another study Khan et al (2013) reported wither height of Azikheli buffalo cows and bulls of Pakistan as 131.35+0.57 cm and 130.01+20.78 cm, respectively which were lower than the observations of present study, whereas (2000) and Kalita et al(2010) in swamp buffaloes of Assam, whereas Vohra et al (2015) reported higher chest girth (195.91±0.67 cm) in Gojri buffaloes of Northern Himalayan India than the present study under field conditions. Goswami (2009) and reported the heart girth little higher in Assamese buffaloes under farm conditions in India and Nili-Ravi buffaloes in Pakistan respectively.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…The average BL in this study was 143.07 cm (Table 1), while the average BL recorded was 142 cm in Murrah buffaloes (Andréa et al 2010), 140 cm in Nili Ravi buffaloes (Ahmad et al 2013), 140 cm in Azikheli buffaloes (Khan et al 2013) and 146 cm in Nili Ravi buffaloes (Kocaman et al 2017). However, longer BL averages were reported in Murrah buffaloes by Dhillod In this study, the average FH recorded was 130.05 cm and the average HH was 130.80 cm (Table 1), indicating that the studied buffaloes have medium stature and medium size.…”
Section: Resultsmentioning
confidence: 53%
“…However, longer BL averages were reported in Murrah buffaloes by Dhillod In this study, the average FH recorded was 130.05 cm and the average HH was 130.80 cm (Table 1), indicating that the studied buffaloes have medium stature and medium size. In Pakistan, Khan et al (2013) registered a higher average FH of 131.35 and an average HH of 123.41 cm in Azikheli buffaloes. In India, Vohra et al (2015) registered an average FH of 128.66 cm in Gojri buffaloes.…”
Section: Resultsmentioning
confidence: 90%